177k views
2 votes
I need answer please help

I need answer please help-example-1
User Harpalss
by
5.1k points

2 Answers

4 votes

Third option


6(3)-4+3^2

Explanation:


f(x) = 4 - {x}^(2) \\ \red{ \bold{ f(3) = 4 - {3}^(2) }} \\ \\</p><p></p><p> g(x) = 6x \\ \purple{ \bold{ g(3) = 6( 3)}} \\ \\ </p><p></p><p>(g - f)(3) = g(3) - f(3) \\ (g - f)(3) = 6( 3) - ( 4 - {3}^(2)) \\ \orange {\boxed {\bold {(g - f)(3) = 6( 3) - 4 + {3}^(2)}}} \\

User Ivan Blinkov
by
4.5k points
1 vote

Answer:

Correct option is the third option:

6*3 - 4+3^2

User Monkeyboy
by
4.0k points